How Composite Materials Influence Sustainable Development : Array - Emin, Anamaria (EuroEconomica, 2021)
Sustainable development has become the most widely accepted concept. Sustainable development refers to the ability of society to develop economically and socially, meeting the requirements of current generations without compromising or risking the chances of future generations. In a broader sense, sustainable development refers to safeguarding the Earth's ability to support life in all its diversity. Especially in the last decade, it has become clear, in the light of climate change, that a more careful use of resources is needed and that all types of emissions must be minimized to reduce the impact of human development and to achieve the sustainable growth. A composite material is an ensemble of distinct materials, which has characteristics that the constituent materials do not have in part. The need to develop new materials and unconventional technologies was determined not only by economic and social reasons, but also by the fact that in the conditions of exponential development of production, there was a very strong crisis of sources of raw materials and energy, with increasing human aggression against the environment. The properties composites offer enable manufacturers to build sustainable attributes into projects or products that may increase energy efficiency, durability and the use of materials that lower environmental impact. The increasing demand for renewable energy, fuel-conserving transportation and greener buildings open a world of opportunity in the composites industry.